Chemosensitization of Trypanosoma congolense strains resistant to isometamidium chloride by tetracyclines and enrofloxacin. - Vincent Delespaux; Hervé Sèna Vitouley; Tanguy Marcotty; Niko Speybroeck; Dirk Berkvens; Krisna Roy; Stanny Geerts; Peter Van den Bossche (Public Library of Science (PLoS), 2010)
BACKGROUND: Because of the development of resistance in trypanosomes to trypanocidal drugs, the livelihood of millions of livestock keepers in sub-Saharan Africa is threatened now more than ever. The existing compounds have become virtually useless and pharmaceutical companies are not keen on investing in the development of new trypanocides. We may have found a breakthrough in the treatment of resistant trypanosomal infections, through the combination of the trypanocide isometamidium chloride (ISM) with two affordable veterinary antibiotics. METHODOLOGY/PRINCIPAL FINDINGS: In a first experiment, groups of mice were inoculated with Trypanosoma congolense strains resistant to ISM and either left untreated or treated with (i) tetracycline, (ii) ISM or (iii) the combination of the antibiotic and the trypanocide. Survival analysis showed that there was a significant effect of treatment and resistance to treatment on the survival time. The groups treated with ISM (with or without antibiotic) survived significantly longer than the groups that were not treated with ISM (P<0.01). The group treated with the combination trypanocide/antibiotic survived significantly longer than the group treated with ISM (P<0.01). In a second experiment, groups of cattle were inoculated with the same resistant trypanosome strain and treated with (i) ISM, (ii) ISM associated with oxytetracycline or (iii) ISM associated with enrofloxacine. All animals treated with ISM became parasitaemic. In the groups treated with ISM-oxytetracycline and ISM-enrofloxacine, 50% of the animals were cured. Animals from the groups treated with a combination trypanocide/antibiotic presented a significantly longer prepatent period than animals treated with ISM (p<0.001). The impact of the disease on the haematocrit was low in all ISM treated groups. Yet, it was lower in the groups treated with the combination trypanocide/antibiotic (p<0.01). CONCLUSIONS/SIGNIFICANCE: After optimization of the administration protocol, this new therapeutic combination could constitute a promising treatment for livestock infected with drug resistant T. congolense.